2020
DOI: 10.3389/fendo.2020.539427
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Intramuscularly or Vaginally Administration May Not Change Live Birth Rate or Neonatal Outcomes in Artificial Frozen-Thawed Embryo Transfer Cycles

Abstract: BackgroundsPrevious studies suggested that singletons from frozen-thawed embryo transfer (FET) were associated with higher risk of large, post-date babies and adverse obstetrical outcomes compared to fresh transfer and natural pregnancy. No data available revealed whether the adverse perinatal outcomes were associated with aberrantly high progesterone level from different endometrium preparations in HRT-FET cycle. This study aimed to compare the impact of progesterone intramuscularly and vaginally regimens on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 44 publications
1
16
2
Order By: Relevance
“…Hence, the impact of E2 on live birth rates could not be accurately assessed. Furthermore, the live birth rates reported in that study were much lower than those in the present study (45.4%) and other research (which were within 35.6%-45.6% [27][28][29][30]). Consequently, other factors, except for the E2 on trigger day, might interfere with the live birth rates for FET cycles in the study conducted by Duan.…”
Section: Resultscontrasting
confidence: 88%
“…Hence, the impact of E2 on live birth rates could not be accurately assessed. Furthermore, the live birth rates reported in that study were much lower than those in the present study (45.4%) and other research (which were within 35.6%-45.6% [27][28][29][30]). Consequently, other factors, except for the E2 on trigger day, might interfere with the live birth rates for FET cycles in the study conducted by Duan.…”
Section: Resultscontrasting
confidence: 88%
“…Now, the route of clinical progesterone administration is intramuscular injection, oral and vaginal administration, or a combination regimen. Current studies suggest that the mode of progesterone administration does not affect pregnancy rates [25][26][27] . Despite these limitations, our study still provides valuable data with reference for clinicians to use exible programmed cycle protocols.…”
Section: Discussionmentioning
confidence: 99%
“…The main characteristics of the included studies are reported in Supplementary Table 1. The included women were recruited during their first or second cycle (19)(20)(21)(22)(23), all of them (24)(25)(26)(27)(28)(29)(30) or not specified (11,14,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). Studies concerned either autologous cycles (13, 14, 19, 21, 22, 25, 27, 29-32, 36, 38-43, 45, 47), oocyte donation (20,44) or not specified (11, 21, 23, 26, 28, 33-35, 37, 46).…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Studies concerned either autologous cycles (13, 14, 19, 21, 22, 25, 27, 29-32, 36, 38-43, 45, 47), oocyte donation (20,44) or not specified (11, 21, 23, 26, 28, 33-35, 37, 46). Studies included single-embryo transfers (11,13,22,28,33,35,40,41), single-or double-embryo transfers (19,20,26,27,30,31,34,37,46), transfers of two to three embryos (24), transfers of three to four embryos (38,39,44) and not reported (14,21,23,25,29,36,43,45,47). Transferred embryos were cleaved embryos (21,24,27,29,34,39), blastocyst embryos (11,13,14,19,20,22,23,26,…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation